THE QUALITY AND SUITABILITY FOR STORAGE OF TOMATO FRUITS DIFFERENT HYBRIDS - Ілюк, Наталя; Завадська, Оксана (SWorldJournal, 2022)
The results of research of indicators of quality and suitability for storage of fresh plum-shaped tomatoes and cherry-type fruits of different hybrids grown in the Forest-Steppe of Ukraine are given. It was studied that the best in terms of quality were